Approaches to the land evaluation and practice of their application in developed countries - Anna Komarova (European Regional Science Association (ERSA), 2013)
Wise land use is an essential basis for steady economic growth. In many developing countries, land usage policy is one of the most troubled areas. An important issue of land usage policies is the process of land value appraisal. It is necessary to study the experience of developed countries in order to make recommendations for the ones which are still developing. Due to standard practice, property is evaluated using three main methodological approaches: comparable sales, cost analysis and income analysis. Techniques of one approach can be used as well as combination of the methods. The choice of method depends on the object of evaluation, available information, type of property usage and others. During mass valuation of real estate comparable sales and income analysis approaches should be preferred in case of assessing the value of multi-family housing when sufficient data on sales and income is available. Approach, based on a comparison of sales, is best suited to evaluate the single-family housing. The cost analysis approach is a good complement to these approaches. As a primary approach it should be applied in the event when there is no sufficient data on sales transactions. The income approach is not suitable for mass estimates of individual single-family housing, as most of this type of property is not rented. Method of determining the value of the land in the developed countries commonly are based either on a comparison of sales, which implies the study of market transactions prices of real estate (Australia, Denmark, Sweden, Indonesia and Japan), or capitalization of income from the potential of the best and most profitable use of real property (some Swiss cantons, some real estate in Denmark and Sweden), or the cost analysis method, which is based on calculating the costs that would be required for a full reconstruction of the property (Indonesia, Japan and South Korea - for buildings), or a combination of all three these methods (U.S., Canada, the Netherlands). Analyzing the experience of the developed countries on land evaluation it can be said that all three main methodological approaches are used. But the practical application of a method of evaluation depends on the type of the object, available information as well as the degree of the market development.
Keywords: R14; R3; 330; land evaluation; cadastre system; evaluation methods